Field notes contributed by James J. Dinsmore, summer 1989 - Dinsmore, James J.et al (1989)
Summer report of birds and locations contributed by James J. Dinsmore. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1989. Epson - sheet feed